Tibetan Opera: A History - Gnanasekaran, R (ASPENSI in Bandung, Indonesia, 2014)
ABSTRACT: The history of Tibet can be traced back to thousand years ago, but the written history dates back to 7th century during the reign of Songtsen Gampo. The first human who appeared in the highest plateau was surrounded by mountains and forest. They were known as Tibetan. Meanwhile, Tibetan Opera reflects the past and keep the history, cultural, and religion of Tibet alive. The word âLhamoâ in Tibetan denotes Goddess. Tibetan Opera was known as âLhamoâ. Because it was believed that when Opera was first performed, there were seven ravishing girls who sang with high-pitched voice in an open air and Thang-stong rGyalpo played the accompanying cymbals and drum. The audience thought that the goddesses hailed from heaven to make a performance. Contemplated by the exquisite voice and beauty, the audience applied the name âLhamoâ to this form of performance. Thang-stong rGyalpo was the pioneer of âLhamoâ. Introducing this kind of performances was mainly for collecting funds that was necessary for the completion of building the Iron Bridge. Further, he collected seven beautiful sisters who were excellent in singing and dancing. Thang-stong rGyalpo trained the seven sisters exactly the same way as the performances of Goddess Khadoma (Dakini) whom he had seen in his vision. Thang-stong rGyalpo and the seven beautiful girls travelled and performed in various Provinces of Central Tibet appealing for funds. Since then, âLhamoâ became a theatrical performance of Tibet.KEY WORD: Tibetan opera, âLhamoâ, Goddess, performance, Thang-stong rGyalpo, Central Tibet, Dalai Lama, and Buddha.Â RESUME: âOpera Tibet: Sebuah Sejarahâ. Sejarah Tibet dapat ditelusuri kembali ke ribuan tahun yang lalu, tapi sejarah yang tertulis kembali ke abad ke-7 pada masa pemerintahan Songtsen Gampo. Manusia pertama yang muncul di dataran tertinggi dikelilingi oleh pegunungan dan hutan. Mereka dikenal sebagai orang Tibet. Sementara itu, Opera Tibet mencerminkan masa lalu dan menjaga sejarah, budaya, dan agama orang Tibet secara hidup. Kata